Influence of Bacillus Safensis and Bacillus Pumilus on the Electrochemical Behavior of 2024-T3 Aluminum Alloy - Paez-Collio, M; Paez-Collio, M (Elsevier B.V., 2022)
In this work, electrochemical techniques were employed to evaluate the contribution to the corrosion and corrosion inhibition of 2024-T3 aluminum alloy by two Gram-positive bacteria. In addition, polarized impedance was used to determine the microbial effect on the cathodic and anodic reactions. These microorganisms were collected from a tropical environment due to the favorable bacterial growth of this kind of climate. The alloy was exposed to the sterile medium and inoculated for up to 12 days evaluating the microbiological and electrochemical behavior. The results by linear scanning voltammetry showed that the B. safensis and B. pumilus caused a dual effect of increase and decrease currents, and through electrochemical impedance spectroscopy, showed in some cases, inductive loop, which could be associated with local corrosion and another case, an increasing impedance could be related to protection. In addition, a morphological characterization was performed by scanning electron microscopy before and after exposure, showing an increase in copper precipitation in the vicinity of the intermetallic phases by bacteria, attributed to local corrosion, but, in general, a significant effect of damages was not observed. © 2021 Elsevier B.V.